Dejavnosti in možnosti izoblikovanja jezika na madžarsko govorečem prostoru in proces Palást - Kolláth, Anna (Slavia Centralis, 2020)
Activities and possibilities for forming language in the Hungarian-speaking space and the Palást process This essay intends to show the results, dilemmas, work, aspects and theoretical motivation behind research group activities underlying language management theory, with the language problem as the focal point (and not language incorrectness). The objective is to uncover, analyse, and solve the most inclusive range of linguistic problems in a language speaking community. The linguistic problem is everything perceived by average speakers in communication, and not problems considered to be such by experts working at certain elite social institutions. It does away with practices of recent language cultivation to an extent that it considers language variations to be a natural linguistic process and by no means a deterioration of the language. It emphasises that language shaping in the language use of minorities inside the Hungarian language community is of even greater importance than in the mother country.